2015
DOI: 10.1148/radiol.14140567
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Diagnostic Performance of Real-time Shear-Wave Elastography

Abstract: Use of a 35-kPa threshold at SWE may provide additional information for the detection and biopsy guidance of prostate cancer, enabling a substantial reduction in the number of biopsies while ensuring that few peripheral zone adenocarcinomas are missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
3
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 49 publications
5
118
3
9
Order By: Relevance
“…In the process of recognizing and selecting associated studies with 11C-choline PET/CT [5,[8][9][10], 18F-FCH PET/ CT [20,44,[49][50][51][52][53][54][55][56][57][58][59][60][61], 11C-acetate PET/CT [7,13,14,62,63], 18F-FDG PET/CT [64][65][66][67][68], TRTE [11,12,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88], and SWE [3,…”
Section: Identification Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of recognizing and selecting associated studies with 11C-choline PET/CT [5,[8][9][10], 18F-FCH PET/ CT [20,44,[49][50][51][52][53][54][55][56][57][58][59][60][61], 11C-acetate PET/CT [7,13,14,62,63], 18F-FDG PET/CT [64][65][66][67][68], TRTE [11,12,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88], and SWE [3,…”
Section: Identification Of the Studiesmentioning
confidence: 99%
“…Specifically, TRTE and SWE could highlight morphologic and biomechanical discrepancies between PCa positive and negative tissues on the basis of ultrasonoscopy [3], while PET/CT might reflect distinctions of metabolic activities inside human body through showing the aggregate state of glucose, protein, nucleic acid, and fatty acid labeled by radiotracers, such as 18F-2-deoxy-2-fluoro-Dglucose (FDG) [4], 11C-choline [5], 18F-fluorocholine (FCH) [6], 11C-acetate [7], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al (19) reported that data analyzed per core regarding SWE findings indicated that for patients with serum PSA <20 ng/ml, the sensitivity and specificity of SWE for prostate cancer detection were 90 and 88%, respectively, while in patients with PSA >20 ng/ml, the sensitivity and specificity were 93 and 93%, respectively. Correas et al (20) reported that the sensitivity, specificity, PPV, NPV and AUC for SWE with a cut-off of 35 kPa for differentiating benign from malignant lesions in 1,040 peripheral zone sextants from 184 patients were 96% (95% CI: 95-97), 85% (95% CI: 83-87), 48% (95% CI: 46-50), 99% (95% CI: 98-100) and 95% (95% CI: 93-97), respectively. In the present study, when combining the cut-off value of 41.0 kPa for tissue elasticity to PI-RADS score, the sensitivity, specificity, PPV and NPV of cancer detection were 70, 98, 91 and 92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated the clinical applications of SWE (19,20). Ahmad et al (19) reported that data analyzed per core regarding SWE findings indicated that for patients with serum PSA <20 ng/ml, the sensitivity and specificity of SWE for prostate cancer detection were 90 and 88%, respectively, while in patients with PSA >20 ng/ml, the sensitivity and specificity were 93 and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It enjoys high levels of intraobserver and interobserver agreement [6]. PSWE has been reported to be useful in noninvasively diagnosis and characterization of different solid tumors, which have been found to be stiffer than the surrounding tissues: e.g., breast lesions [7], prostate cancer [8], thyroid cancer [9], lymph nodes [10] and pancreatic masses [11]. Beyond CEUS, CT or MRI, it may help discriminating malignant versus benign masses, particularly with regard to patients unsuitable for contrast enhanced imaging [12].…”
Section: Introductionmentioning
confidence: 99%